Overcoming CEP85L-ROS1, MKRN1-BRAF and MET amplification as rare, acquired resistance mutations to Osimertinib - Kian, Waleed; Krayim, Bilal; Alsana, Hadel; Giles, Betsy; Purim, Ofer; Alguayn, Wafeek; Alguayn, Farouq; Peled, Nir; Roisman, Laila C. (Frontiers in Oncology, 2023)
Lung cancer is the most common cancer-related cause of death worldwide, most of which are non-small cell lung cancers (NSCLC). Epidermal growth factor receptor (EGFR) mutations are common drivers of NSCLC. Treatment plans for NSCLC, specifically adenocarcinomas, rely heavily on the presence or absence of specific actionable driver mutations. Liquid biopsy can guide the treatment protocol to detect the presence of various mechanisms of resistance to treatment. We report three NSCLC EGFR mutated cases, each treated with Osimertinib in a combination therapy regimen to combat resistance mechanisms. The first patient presented with EGFR L858R/L833V compound mutation with MET amplification alongside CEP85L-ROS1 fusion gene, the second with EGFR exon 19del and MKRN1-BRAF fusion, and the last EGFR L858R/V834L compound mutation with MET amplification. Each regimen utilized a tyrosine kinase inhibitor or monoclonal antibody in addition to osimertinib and allowed for a prompt and relatively durable treatment response.